An Exploratory Analysis of Happiness at Workplace from Malaysian Teachers Perspective Using Performance-Welfare Model - Abdullah, Abdul Ghani Kanesan; Ling, Ying-Leh; Peng, Chen Siew (International Journal of Asian Social Science, 2016)
The purpose of this study is to investigate the characteristics of welfare at workplace using Wellness-Performance Model in the context of Malaysian teachers ‘perspective. This study was carried out by using a combination of qualitative and quantitative method in two different phases. In the first phase, the focus group discussions were conducted while the questionnaire used in a second phase to indicate the respondents’ feelings about the workplace welfare. In this research, a total of 10 public school teachers involved throughout the first phase. Meanwhile, 180 trained teachers randomly selected to take part in this study for the second phase. All the discussions were recorded for the exploratory and descriptive qualitative study using the Performance - Welfare Medal. Next, the data obtained in second phase analyzed by using descriptive statistics. As a result, it is revealed that all five components, namely the teachers' contribution, teachers trust, school climate, teacher involvement, and teacher confidence, to achieve individual potential with the support of the trust, recognition, and pride.